Do walkable neighborhoods promote physical activity؟ - ameneh marzban; Masoud Soleymani-rad (Shahid Sadoughi University of Medical Sciences, 2022)
The American Society of Surgeons recommends that at least 30 minutes of moderate-intensity physical activity be performed daily for at least five days a week to ensure the minimum physical health of citizens. Follow these tips because there are not enough spaces, suitable, safe and secure for physical activity and sports for citizens or very rare (1).